CLINICAL ASPECTS OF ALCOHOLISM IN PERSONS WITH ASSOCIATED PERSONALITY DISORDERS (World Bulletin of Public Health, 2024)
Ongoing research aimed at identifying the mechanisms of the emergence and persistence of addictive disorders, which is the main factor that worsens the indicators of the narcological situation. Mental disorders combined with alcohol addiction are increasingly becoming objects of close study, since they exist at the junction of two specialties – narcology and psychiatry, thereby causing difficulties in medical examination, prevention and treatment of patients.
Keywords: alcohol dependence; mental disorders; comorbid course.